Bcr1 plays a central role in the regulation of opaque cell filamentation in Candida albicans - Guan, Guobo (2013)
The human fungal pathogen Candida albicans has at least two types of morphological transitions: white to opaque cell transitions and yeast to hyphal transitions. Opaque cells have historically not been known to undergo filamentation under standard filament-inducing conditions. Here we find that Bcr1 and its downstream regulators Cup9, Nrg1 and Czf1 and the cAMP-signaling pathway control opaque cell filamentation in C. albicans. We have shown that deletion of BCR1, CUP9, NRG1 and CZF1 results in opaque cell filamentation under standard culture conditions. Disruption of BCR1 in white cells has no obvious effect on hyphal growth, suggesting that Bcr1 is an opaque-specific regulator of filamentation under the conditions tested. Moreover, inactivation of the cAMP-signaling pathway or disruption of its downstream transcriptional regulators, FLO8 and EFG1, strikingly attenuates filamentation in opaque cells of the bcr1/bcr1 mutant. Deletion of HGC1, a downstream gene of the cAMP-signaling pathway encoding G1 cyclin-related protein, completely blocks opaque cell filamentation induced by inactivation of BCR1. These results demonstrate that Bcr1 regulated opaque cell filamentation is dependent on the cAMP-signaling pathway. This study establishes a link between the white-opaque switch and the yeast-filamentous growth transition in C. albicans.